Good Governance Principles: The Process of Legal Documentation and Information Networks in Sumedang Regency - Edrick Akbar; Andre Ariesmansyah (Formosa Journal of Social Sciences (FJSS), 2024)
The principle of Good Governance in general is a concept that refers to the process of achieving decisions and their implementation that can be accounted for together well. As a consensus reached by the government, citizens, and the private sector for the implementation of government in a country. Examining the implementation of Good Governance to determine policies in the Sumedang Regency Legal Secretariat which is the current public service paradigm to serve the community optimally. This study aims to describe and analyze the implementation of good governance in the process of making legal products of the Sumedang Regency Regional Secretariat. In this study, the researcher used a qualitative approach to secondary data with a descriptive writing method. Implementation of the Principles of Good Governance according to the (United Nation Development Programme), 1997, the Sumedang Regency Legal Secretariat has made efforts to fulfill the principles of Good Governance by creating services that can be easily accessed via the internet network.is a system that aims to provide easy, transparent and accurate access to legal information